EFEKTIVITAS PENGGUNAAN MEDIA PRAKTIKUM TERHADAP PENINGKATAN PEMAHAMAN PESERTA DIDIK PADA MATERI PERUBAHAN WUJUD BENDA DI KELAS III SEKOLAH DASAR - Nur Maulida Isnaeni, - (2023)
This research is motivated by the lack of educators in trying learning media. This affects the understanding of students, especially in the material changes in the form of objects. Material changes in the form of objects really need appropriate learning media. Judging from this background, the researchers tested practicum media to increase students' understanding of science lessons. The purpose of this study was to measure, describe, and find out the significance of increasing the understanding abilities of class III students at SDN 4 Sindanggalih and SDN 5 Sindanggalih in learning natural science about changes in the shape of objects before and after using practicum media. The research method used was a quasi-experimental design with a population of class III students at SDN 4 Sindanggalih and SDN 5 Sindanggalih, totaling 39 students. The instrument used is a matter of pretest and posttest. The results showed that the average understanding of students seen from the results of the pretest of students was 3.07, while the average understanding of students was seen from the posttest score of 8.53. Based on the results of the pretest and posttest there was an increase of 54%. Keywords: practicum media, understanding, changes in the form of objects